2012
DOI: 10.1371/journal.pone.0043724
|View full text |Cite
|
Sign up to set email alerts
|

Developmental Regulation of Protein O-GlcNAcylation, O-GlcNAc Transferase, and O-GlcNAcase in Mammalian Brain

Abstract: O-GlcNAcylation is a common posttranslational modification of nucleocytoplasmic proteins by β-N-acetylglucosamine (GlcNAc). The dynamic addition and removal of O-GlcNAc groups to and from proteins are catalyzed by O-linked N-acetylglucosamine transferase (O-GlcNAc transferase, OGT) and β-N-acetylglucosaminidase (O-GlcNAcase, OGA), respectively. O-GlcNAcylation often modulates protein phosphorylation and regulates several cellular signaling and functions, especially in the brain. However, its developmental regu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1

Citation Types

4
84
0

Year Published

2012
2012
2022
2022

Publication Types

Select...
7
2

Relationship

1
8

Authors

Journals

citations
Cited by 84 publications
(88 citation statements)
references
References 41 publications
4
84
0
Order By: Relevance
“…In our study only one OGT isoform, ncOGT, could be detected and analysis of IPL and cerebellar samples revealed that ncOGT protein levels were unaffected in AD. In rat brain sOGT expression declined after maturation and no mOGT expression could be detected in adult brain [39] which may explain why no mOGT and sOGT were detected in our study. Investigation of OGT activity is necessary to allow for a meaningful discussion of the influence of OGT on O-GlcNAcylation in AD as altered or unaltered protein levels may not reflect changes in enzyme activity.…”
Section: Discussionmentioning
confidence: 80%
“…In our study only one OGT isoform, ncOGT, could be detected and analysis of IPL and cerebellar samples revealed that ncOGT protein levels were unaffected in AD. In rat brain sOGT expression declined after maturation and no mOGT expression could be detected in adult brain [39] which may explain why no mOGT and sOGT were detected in our study. Investigation of OGT activity is necessary to allow for a meaningful discussion of the influence of OGT on O-GlcNAcylation in AD as altered or unaltered protein levels may not reflect changes in enzyme activity.…”
Section: Discussionmentioning
confidence: 80%
“…OGA activity decreased after birth, whereas OGT activity increased after birth such that both reached stable levels postnatally. Immunohistochemical staining for O-GlcNAc, as well as OGA and OGT, revealed developmental changes in staining, but in postnatal mice, these markers all showed a similar distribution in the brain, with the greatest immunoreactivity being present within all classes of neurons throughout all regions of the brain (52). Other studies reported particularly high levels of OGT expression and O-GlcNAc in the cerebellar cortex and hippocampus (53,54).…”
Section: O-glcnac and O-glcnac-processing Enzymes Are Particularly Abmentioning
confidence: 87%
“…In mice, one study found higher brain O-GlcNAc at 5 months compared with 3 or 13 months (51). The most rigorous study (52), in which O-GlcNAc , OGA, and OGT levels in rat brain were monitored from embryos to 2 years of age, showed that O-GlcNAc levels were most abundant in prenatal rats, and soon after birth, levels became stable. This study also showed variation in the levels of OGT splice variants and the activities of both OGT and OGA.…”
Section: O-glcnac and O-glcnac-processing Enzymes Are Particularly Abmentioning
confidence: 99%
“…Brain O-GlcNAcylation is modulated during development and neurotransmission, suggesting potential regulatory roles of O-GlcNAc in these processes (2)(3)(4)(5)(6)(7). Current knowledge is still insufficient to draw a clear picture for the physiological function of O-GlcNAc signaling in the brain, but there is growing evidence that O-GlcNAc may regulate synaptic plasticity, a property of neurons to modulate the strength of communication between synapses that is indispensible for learning and memory (6,8).…”
Section: O-glcnac and Enzymes Executing Its Turnover (O-glcnac Transfmentioning
confidence: 99%